HEMATOLOGICAL EVALUATION IN UNTREATED PARACOCCIDIOIDOMYCOSIS-PATIENTS - Moris, DV; Moreto, TC; Cavalcante, RS; Arantes, TD; Carvalho, LR; Mendes, RP (Revista do Instituto Adolfo Lutz, 2009)
Introduction. Paracoccidioidomycosis (PCM) is a systemic granulomatous disease restricted to Latin America that frequently disseminates to several organs. The clinical evaluation of PCM-patients is frequently completed by laboratory tests. The objective of this study is to evaluate some hematological variables in untreated patients. Patients and Methods. We studied 83 patients with PCM confirmed by identification of the etiological agent or detection of serum antibodies by double agar gel immunodiffusion test, clinically classified according to Mendes (1994): 29 presented the acute/subacute severe form (G1), 35 the chronic moderate form (G2) and 19 the chronic severe form (G3). Hematological exams were performed in routine clinical laboratories at the University Hospital – UNESP. Comparison of medians were carried out by KruskalWallis test and significance was set up at p<0.05. Results. Hemoglobin (g%) [G1=11.1; G2=15.1; G3=14.6] and hematocrit (%) [G1=34.5; G2=44.2; G3=43.4] showed low values only in G1 [G1<(G2=G3)]; eosinophils count (no./mm3 ) [G1=616; G2=430; G3=256] was increased only in G1 [G1>(G2=G3)]; platelet count (no./mm3 ) [G1=380,500; G2=311,000; G3=358,000] was normal in all the groups, but with difference among them [G2<(G1=G3)]; neutrophils [G1=5,519; G2=6,360; G3=6,6,832], total lymphocytes [G1=1,821.5; G2=2,121; G3=2,125] and monocytes [G1=480; G2=485; G3=820] count were normal (G1=G2=G3). Erythrocyte sedimentation rate (mm/1st hour) [G1=43; G2=29; G3=30] was always increased [G1>(G2=G3)]. Conclusions. The hematological alterations caused by P. brasiliensis suggest careful follow-up of PCM-patients, with routine evaluation of the hemogram and erythrocyte sedimentation rate.